Research progress in the application of aptasensors for mycotoxins detection - YUAN Jinglei; LI Na (Zhongguo shipin weisheng zazhi, 2023)
Mycotoxins are toxic metabolites produced by fungi in contaminated food， which can cause acute or chronic poisoning in humans. Therefore， the rapid and accurate detection method for mycotoxins is essential to ensure food safety. Aptamers are short single-stranded deoxyribonucleic acid or ribonucleic acid molecules， which， as recognition elements， have the advantages of being specific， stable， and easy to synthesize and modify. Aptasensors have been widely used in mycotoxins detection. This paper summarizes various application examples of aptasensors in mycotoxins detection and provides ideas and methods for realizing the fast， accurate， and efficient detection of mycotoxins.